The Business Educator after Graduation: Beginning of a New Era as an Entrepreneur - Sani, Ibrahim (NIU Journal of Humanities, 2018)
The paper argued that the business education graduate can perform successfully as an entrepreneur because the main objective of the business education program at all levels of the educational system, particularly at the university level, is to inculcate in the individual practical skills that will make him fit into the world of work either as an employee, self-employed or as an employer.  However, success as a self-employed person requires entrepreneurship skills.  The paper explained the link between the objectives of the business education program and success as an entrepreneur, identifying the various areas - such as establishment and running of shops for the repair and sales of cell phones, establishment and running of bookshops, establishment and running of barbing and hair dressing saloons, establishment and running of restaurants - that the business education graduate can venture into as an entrepreneur. The paper concluded that graduating from school should be something worth looking forward to, because the world is full of opportunities.  It however cautioned that to become a successful entrepreneur is not an easy thing; there will be huddles to cross. Becoming a successful entrepreneur requires tenacity, focus, perseverance and a firm belief in oneâ€™s ability to succeed. The paper made five recommendations. One of them is that the business educator should look around and identify the opportunities that abound. Another recommendation made is that after identifying an opportunity, the business educator should draw up a business plan that he will be able to convince sponsors to finance.